The book of joy : lasting happiness in a changing world - Bstan- dzin-rgya-mtsho, Dalai Lama XIV, 1935-; Tutu, Desmond (Avery, 2016)
Two leading spiritual masters share their wisdom about living with joy even in the face of adversity, sharing personal stories and teachings about the science of profound happiness and the daily practices that anchor their emotional and spiritual lives.